PENGEMBANGAN APLIKASI PENGKELASAN MUTU BUAH TOMAT BERDASARKAN BOBOT BUAH MENGGUNAKAN PENGOLAHAN CITRA DIGITAL DENGAN ANALISIS REGRESI - I Komang Mudana (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This application development is aimed to classify the quality of tomatoesusing digital image processing, so that the quality of tomatoes classification process can be done more effectively and efficiently. The use of new techniques in agriculture will help to optimize agricultural production. Department of Agriculture in cooperation with the Bogor Agricultural Institute (IPB) has developed an application of Pontianak Oranges classification by size and color using image processing aimed to evaluate the quality of the fruit by size and color of the fruit.An effective and efficient quality classifications process of tomato is required to maximize the production of tomatoes. The Quality classification process of the tomatoes using digital image processing with connected component labeling algorithm would compute the amount of tomato and the number of pixels of each tomato. The number of pixels and weight samples first inserted to the regression equation to find the relationship between the number of pixels and the weight of the tomato. The tested tomato image then inserted to determine the number of pixels the of the tomato image. By using the regression equation formed before and the number of pixel the tomato, will be known the weight and quality of each tested tomato is.This application implemented in a desktop based software which isdeveloped using Borland Delphi 7. This application uses a web camera (webcam) to take image of tomatoes both the sample and the test fruit. The images obtained are then processed so the quality of tested tomatoes can be seen.